Safely removing cell debris with LC3‐associated phagocytosis. (25th August 2017) - Fazeli, Gholamreza; Wehman, Ann Marie
Abstract: Phagocytosis and autophagy are two distinct pathways that degrade external and internal unwanted particles. Both pathways lead to lysosomal degradation inside the cell, and over the last decade, the line between them has blurred; autophagy proteins were discovered on phagosomes engulfing foreign bacteria, leading to the proposal of LC3‐associated phagocytosis (LAP). Many proteins involved in macroautophagy are used for phagosome degradation, although Atg8/LC3 family proteins only decorate the outer membrane of LC3‐associated phagosomes, in contrast to both autophagosome membranes. A few proteins distinguish LAP from autophagy, such as components of the autophagy pre‐initiation complex. However, most LAP cargo is wrapped in multiple layers of membranes, making them similar in structure to autophagosomes. Recent evidence suggests that LC3 is important for the degradation of internal membranes, explaining why LC3 would be a vital part of both macroautophagy and LAP. In addition to removing invading pathogens, multicellular organisms also use LAP to degrade cell debris, including cell corpses and photoreceptor outer segments. The post‐mitotic midbody remnant is another cell fragment, which results from each cell division, that was recently added to the growing list of LAP cargoes. Thus, LAP plays an important role during the normal physiology and homoeostasis of animals. Abstract : Review : LC3‐associated phagocytosis is a non‐canonical form of autophagy, where autophagy proteins are recruited to phagosomes. Cells use LC3‐associated phagocytosis to degrade pathogens as well as cell corpses and cell debris. LC3‐associated phagosomes contain an inner membrane and present LC3 on their outer membrane. LC3 may be required on the surface of autophagosomes and LC3‐associated phagosomes for the degradation of inner membranes and thereby cargo.